2017
DOI: 10.5194/amt-10-4877-2017
|View full text |Cite
|
Sign up to set email alerts
|

An intercomparison of HO<sub>2</sub> measurements by fluorescence assay by gas expansion and cavity ring-down spectroscopy within HIRAC (Highly Instrumented Reactor for Atmospheric Chemistry)

Abstract: Abstract. The HO2 radical was monitored simultaneously using two independent techniques in the Leeds HIRAC (Highly Instrumented Reactor for Atmospheric Chemistry) atmospheric simulation chamber at room temperature and total pressures of 150 and 1000 mbar of synthetic air. In the first method, HO2 was measured indirectly following sampling through a pinhole expansion to 3 mbar when sampling from 1000 mbar and to 1 mbar when sampling from 150 mbar. Subsequent addition of NO converted it to OH, which was detected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 62 publications
0
50
0
Order By: Relevance
“…where S R i O 2 /S HO 2 is the sensitivity of ECHAMP to individual RO 2 compounds relative to that of HO 2 , L i is the fractional sampling transmission of an individual organic peroxy species R i O 2 through the short inlet into the reaction chambers (relative to that of HO 2 ), Y is the alkyl nitrate yield (Y = R8b/(R8a + R8b)), and the remaining terms in parentheses account for alkyl nitrite (RONO) formation. Alkyl nitrate yields increase with the carbon backbone number, from less than 0.1 % for CH 3 O 2 to 8 % for isoprene and to over 25 % for C10 and larger alkyl peroxy radicals (Lockwood et al, 2010;Orlando and Tyndall, 2012). Alkyl nitrite (RONO) formation accounts for less than a 4 % loss for most organic peroxy radicals and is likely negligible for alkene-derived peroxy radicals due to the rapid decomposition of β-hydroxy alkoxy radicals (Atkinson, 1997) but can sequester a calculated 10 % loss of CH 3 O 2 (Wood et al, 2017).…”
Section: Echamp Measurements Of Total Peroxy Radicals (Xo 2 )mentioning
confidence: 99%
“…where S R i O 2 /S HO 2 is the sensitivity of ECHAMP to individual RO 2 compounds relative to that of HO 2 , L i is the fractional sampling transmission of an individual organic peroxy species R i O 2 through the short inlet into the reaction chambers (relative to that of HO 2 ), Y is the alkyl nitrate yield (Y = R8b/(R8a + R8b)), and the remaining terms in parentheses account for alkyl nitrite (RONO) formation. Alkyl nitrate yields increase with the carbon backbone number, from less than 0.1 % for CH 3 O 2 to 8 % for isoprene and to over 25 % for C10 and larger alkyl peroxy radicals (Lockwood et al, 2010;Orlando and Tyndall, 2012). Alkyl nitrite (RONO) formation accounts for less than a 4 % loss for most organic peroxy radicals and is likely negligible for alkene-derived peroxy radicals due to the rapid decomposition of β-hydroxy alkoxy radicals (Atkinson, 1997) but can sequester a calculated 10 % loss of CH 3 O 2 (Wood et al, 2017).…”
Section: Echamp Measurements Of Total Peroxy Radicals (Xo 2 )mentioning
confidence: 99%
“…Therefore, a series of experiments was conducted to quantify the initial amount of radicals. This was achieved by quantitatively converting all Cl-atoms to HO 2 radicals, which can be reliably measured by cw-CRDS on a strong absorption line at 6638.205 cm −1 [23,[26][27][28][29] . The measurement of the HO 2 absorption cross section is based on the measurement of HO 2 decays during self-reaction, which allows for retrieval of the initial concentration, and thus the absorption cross section, if the rate constant is known.…”
Section: Resultsmentioning
confidence: 99%
“…We have not quantified these losses, but with an estimated residence time of 1 s in the cavity, an initial concentration of 10 11 cm −3 would reduce by 26% within 1 s, based on a self-reaction rate of 1.79 × 10 −12 cm 3 s −1 . 21 spectrometer allows for retrieval of absorption coefficient, α, and θ values from the same data set based on (A33) and 2, respectively. Ring-down measurements were acquired across the spectral region with a step size of 0.0036 cm −1 with 200 RDTs averaged (integration time: ∼2 s) for each spectral data point.…”
Section: Resultsmentioning
confidence: 99%
“…20 Onel et al demonstrated a sensitivity of 3.0 × 10 8 cm −3 for HO 2 at a total sample pressure of 150 mbar using CRDS at 1506 nm. 21 In the context of radical detection, HO 2 also possesses a nonzero magnetic moment and is therefore susceptible to the Faraday effect, i.e., the polarization of a linearly polarized light wave propagating in the same direction as an applied magnetic field will be rotated when it travels through the paramagnetic sample. The Faraday effect is a consequence of magnetic circular birefringence (MCB) induced by the Zeeman effect, in which left-hand circularly polarized (LHCP) and right-hand circularly polarized (RHCP) waves experience different refractive indices.…”
mentioning
confidence: 99%